Strategy Management with SWOT Analysis to Increase the Potential of Pos Ketan Legenda 1967 as a Hits Culinary Tourism Place in Batu City - Kamelia Arifah; Suharto, Bambang (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Pos Ketan Legenda 1967 is one of the culinary hits of Batu City with more than 10 branches spread across various regions and cities. The branch of Pos Ketan Legenda centered in Batu Tourism City, East Java serves typical and warm food. The main food sold is sticky rice sprinkled with misis, cheese, soy powder, durian and others. This research aims to analyze the potential of Pos Ketan Legenda 1967 as a culinary tourism attraction to be widely known by people from various regions to maintain a family business that has been running since 1967. The research method used is descriptive qualitative using SWOT analysis. The informants of this research are the owner of Pos Ketan Legenda 1967 located in Batu City, employees, and customers of Pos Ketan Legenda 1967 in Batu City. The results showed that there are strategies that can be carried out by Pos Ketan Legenda 1967 Batu City by utilizing existing strengths and opportunities and minimizing existing weaknesses and threats. This study also indicates that a family business that has been established since 1967 such as Pos Ketan Legenda 1967 certainly also has weaknesses and will continue to face threats around such as the emergence of fast food culinary such as street food. The need for a digital marketing strategy to be able to maintain its business existence like other businesses.